Analyzing the Research and Application of the RSA Cryptosystem in the Context of Digital Signatures - Ding, Mashuo (Transactions on Computer Science and Intelligent Systems Research, 2024)
The article commences by laying the foundational knowledge of public key cryptographic systems, with a focus on RSA encryption and digital signature technology. It then utilizes RSA encryption as a paradigm to elucidate the application of this encryption in digital signature schemes, offering an algorithmic perspective. A critical link is established between the security of digital signatures and the robustness of RSA public key cryptographic systems. Subsequently, the article presents a concise overview of the potential threats facing RSA encryption and proposes pertinent strategies to mitigate these security challenges. It culminates in a synthesis of three distinct approaches, encompassing both algorithmic and hardware aspects, to augment the efficiency of modular exponentiation – a key operation in RSA encryption. Since the inception of the RSA public key cryptosystem, it has been subject to continuous refinement, standardization, and practical deployment. Enhancing the computational efficiency and security of RSA encryption remains a pivotal area of research and discussion within the cryptographic community. Furthermore, with the progressive advancements in quantum theory, traditional public key systems, including RSA and elliptic curve cryptography, confront emerging security vulnerabilities. Thus, the pursuit of post-quantum cryptography, capable of withstanding quantum attacks, represents a frontier scientific endeavor in the field of cryptography.